Molecular pathogenesis of human prostate basal cell hyperplasia. Issue 13 (10th August 2017) - Henry, Gervaise; Malewska, Alicia; Mauck, Ryan; Gahan, Jeffrey; Hutchinson, Ryan; Torrealba, Jose; Francis, Franto; Roehrborn, Claus; Strand, Douglas
Abstract : Background: Understanding the molecular pathogenesis of distinct phenotypes in human benign prostatic hyperplasia (BPH) is essential to improving therapeutic intervention. Current therapies target smooth muscle and luminal epithelia for relief of lower urinary tract symptoms (LUTS) due to BPH, but basal cell hyperplasia (BCH) remains untargeted. The incidence of has been reported at 8‐10%, but a molecular and cellular characterization has not been performed on this phenotype. Methods: Using freshly digested tissue from surgical specimens, we performed RNA‐seq analysis of flow cytometry‐purified basal epithelia from 3 patients with and 4 patients without a majority BCH phenotype. qPCR was performed on 28 genes identified as significant from 13 non‐BCH and 7 BCH specimens to confirm transcriptomic analysis. IHC was performed on several non‐BCH and BCH specimens for 3 proteins identified as significant by transcriptomic analysis. Results: A total of 141 human BPH specimens were analyzed for the presence of BCH. Clinical characteristics of non‐BCH and BCH cohorts revealed no significant differences in age, PSA, prostate volume, medical treatment, or comorbidities. Quantitation of cellular subsets by flow cytometry in 11 BCH patients vs. 11 non‐BCH patients demonstrated a significant increase in the ratio of basal to luminal epithelia in patients with BCH (P <0.05), but no significant differences in the total number of leukocytes. RNA‐seq data from flow cytometry isolated basal epithelia from patients with and without BCH were subjected to gene set enrichment analysis of differentially expressed genes, which revealed increased expression of members of the epidermal differentiation complex. Transcriptomic data were complemented by immunohistochemistry for members of the epidermal differentiation complex, revealing a morphological similarity to other stratified squamous epithelial layers. Conclusions: Increased expression of epidermal differentiation complex members and altered epithelial stratification resembles the progression of other metaplastic diseases. These data provide insight into the plasticity of the human prostate epithelium and suggest a classification of basal cell hyperplasia as a metaplasia.